MANAGING CREATIVITY IN CHANGE: Motivations and constraints of creative work in a media organisation. (16th November 2016) - Malmelin, Nando; Virta, Sari
Abstract : This article is concerned with the management of creative journalistic work in a media organisation. It reports and analyses a case study conducted in one of Europe's largest media corporations: the focus of the study was a development team of journalists set up and charged with creating and producing a new multi-platform media service and its content. The article discusses the ways in which the creativity of media professionals is supported and managed under the constantly changing conditions of media work and journalistic practices. The study contributes to research on creativity in the media industry, particularly the management of creativity in journalism and media work. The findings identify the key motivations and constraints in relation to creative journalistic work in the media industries under digital transformation. Specifically, media professionals are motivated by the opportunity for developing new skills and competencies as well as chances to create new journalistic products and practices. The article suggests that the skills of change management, communication management and project management are crucial for creative media work.